Behavioral analysis for mode choice of commuters in Dhaka City, Bangladesh for introducing Bus Rapid Transit System (BRTS) - Noor-E-Alam; Kim, Hyunmyung; Pichai Taneerananon; Kunnawee Kanitpong; Joint Japan/World Bank Graduate Scholarship Program (JJ/WBGSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
The congestion, safety and environmental problems are rapidly increasing due to the combined effects of rapid motorization and urbanization in Dhaka city, the capital of Bangladesh. Mass rapid transport can address these problem by proving enough rider ship, safe journey and less emission with modem technology as sustainable mode. This research aims to carryout in-depth study about travel behavior of Dhaka city giving more focus on introducing a new mode, Bus rapid transit. Existing public transport attributes were examined both in importance and satisfaction level for fixing the new BRT attributes. A stated preference survey was conducted to see the possible willingness of the commuters to shift from their current mode to newly proposed Bus rapid transit. Survey results showed that female travelers prefer to use taxilCNG & non-motorized vehicle more than male as these modes are comfortable, personalized and can give door to door service which is convenient for female. As household income increases people are more inclined to personalized mode. Loosing wallet to pickpockets are very common especially in crowded public buses in Dhaka. Short distance trips are made by walk, rickshaw and Para transit while buses are used mostly for long distance. Travel time ,Priority seat for women and special need people, cost ,in vehicle security frequency of service, and in vehicle comfort were found to be the most important attribute for public transport in context of Dhaka city. Most of the respondents showed their total dissatisfaction with existing public transport attributes. Due to the dissatisfaction with almost all existing attributes of the public transport in Dhaka city majority of the respondents showed positive attitude about BRT. Some private car users and NMV users do not want to switch to BRT because private car is comfortable and secured and NMV gives door to door service. Middle income group was found to be the most potential group to switch to BRT New BRT system should have comfortable riding facility, be reliable and secured, easily accessible and should have priority seat for female and special need people in order to attract the commuters of Dhaka city.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Transportation Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2008
Keywords: Bus rapid transit -- Bangladesh -- Dhaka; Transportation -- Bangladesh -- Dhaka